Law Enforcement in Indonesian Maritime Areas: Opportunities and Challenges - Irma Rachmawati Maruf (Sean Institute, 2024)
Law enforcement in Indonesian maritime areas is an important subject in the context of sustainability of marine resources and protection of the maritime environment. This research aims to explore the opportunities and challenges related to law enforcement in Indonesian maritime areas. The research method used is descriptive analysis by collecting data from various primary and secondary sources using a normative legal approach. The research results show that in law enforcement in Indonesian maritime areas, there are great opportunities that can be exploited, such as natural resource wealth, international cooperation, technology and innovation, as well as investment in the marine and fisheries sector. However, the research also identified several challenges, including budget, personnel, and technology limitations, the rapid pace of technological change, legal diversity, and competition with other countries. To overcome this challenge, a strong commitment from the government is needed to increase investment, training, cross-sectoral and cross-institutional coordination, as well as readiness to face the impacts of climate change and extreme weather. With a comprehensive approach, Indonesia can maximize its maritime potential while maintaining environmental sustainability and improving the welfare of coastal communities.